The design of eLearning resources for Ibec Global Graduates 2 - Hennigan, Rowena (Henry Stewart Talks, 2020)
Virtual learning environment (VLE), Distance delivery, Ibec Global Graduates (IGG) programme, Learning management system (LMS)